2020
DOI: 10.1002/rmb2.12355
|View full text |Cite
|
Sign up to set email alerts
|

Male advantage observed for in vitro fertilization mouse embryos exhibiting early cleavage

Abstract: Sex ratio skews have frequently been reported among mammals. 1 In mice, it has been reported that mouse embryos forming blastocoele early versus those forming late are predominantly male. 2,3 Although it has been reported that sex-determining region genes, Sry and Zfy, are transcribed as early as the 2-cell stage in mouse embryos, 4 a male advantage at earlier stage of embryonic development than blastocyst stage has not been examined yet. It might be possible that the male advantage could be recognized at an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…Regarding “poor-quality embryos”, developed/cleavaged embryos were selected (at 2–4-6 cells) at 53 h, with intact and good morphology of the cells. These “poor-quality” embryos could have stopped the development, or have an altered development or be only “very slow”, since part of them reached the blastocyst stage (blastocyst rate 11%), in line with previous studies [ 42 45 ]. Since more likely, there was a mix of blocked, altered but also simply delayed embryos, we did not call them “bad quality embryos” or embryos with impaired development.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Regarding “poor-quality embryos”, developed/cleavaged embryos were selected (at 2–4-6 cells) at 53 h, with intact and good morphology of the cells. These “poor-quality” embryos could have stopped the development, or have an altered development or be only “very slow”, since part of them reached the blastocyst stage (blastocyst rate 11%), in line with previous studies [ 42 45 ]. Since more likely, there was a mix of blocked, altered but also simply delayed embryos, we did not call them “bad quality embryos” or embryos with impaired development.…”
Section: Discussionsupporting
confidence: 85%
“…The timing to assign embryos to good- or poor-quality embryo groups was based on the objectives of the study, the experimental conditions, and previous studies [ 42 45 ]. According to these studies, selecting embryos at 53 h postinsemination allows to have a pool of embryos with fast, moderate, and slow development in the “good-quality embryos” group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have suggested that blastocyst transfer can increase the proportion of male embryos (3,36,37). Because male embryos develop faster than female embryos and have better morphology, the faster-growing embryos are more likely to be male (38). Additionally, studies have shown that compared with female embryos developed during the same period, the morphological score of male embryos was better; for example, 72% of D5 or D6 blastocysts were male embryos, whereas 60% of D3 blastocysts were female embryos (39).…”
Section: Discussionmentioning
confidence: 99%
“…IVF was performed as previously described [ 24 ]. Young female ICR mice (3–6 weeks old) and adult male ICR mice (14–20 weeks old) were used for fertilization.…”
Section: Methodsmentioning
confidence: 99%